2005
DOI: 10.1038/sj.bjp.0706333
|View full text |Cite
|
Sign up to set email alerts
|

Some structural determinants of the antiproliferative effect of heparin‐like molecules on human airway smooth muscle

Abstract: 1 Accumulation of airway smooth muscle (ASM) and its infiltration by mast cells are key pathological features of airway remodelling in asthma. Heparin, a major component of mast cell granules, inhibits ASM proliferation by an unknown mechanism. Here, unfractionated heparins and related glycosaminoglycans having structurally heterogeneous polysaccharide side chains that varied in molecular weight, sulphation and anionic charge were used to identify features of the heparin molecule that were required for its ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Some information is available in the literature on the effect of GAGs on cell proliferation. Several investigators have reported that heparin and heparin-like molecules can reduce proliferation of HASMCs (9,19). In his experiments, Kanabar et al (19) showed that chondroitin sulfate A and B had less marked effects despite concentrations much greater (up to 10 mg/ml) than those used in the current experiment.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Some information is available in the literature on the effect of GAGs on cell proliferation. Several investigators have reported that heparin and heparin-like molecules can reduce proliferation of HASMCs (9,19). In his experiments, Kanabar et al (19) showed that chondroitin sulfate A and B had less marked effects despite concentrations much greater (up to 10 mg/ml) than those used in the current experiment.…”
Section: Discussionmentioning
confidence: 60%
“…Versican, the large aggregating PG, can either enhance or decrease vascular smooth muscle proliferation, depending on the specific versican isoform (37). Heparin, the glycosaminoglycan side chain bound to basement membrane PG, has been shown to have antiproliferative effects on human and canine ASM (9,19).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in COPD patients [34] or elastase-induced emphysema [35], treatment with HA had beneficial effects. It is of interest that two other GAG, heparin and HS, have also been reported to be beneficial during asthma therapy by a mechanism of action that is not directly related to their anticoagulant property [36].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inhibition of vascular smooth muscle proliferation is a long established property of heparin (Clowes and Karnowsky, 1977), unrelated to anticoagulant activity (Guyton et al, 1980), that has since been described in airway smooth muscle as well (Kilfeather et al, 1995;Okona-Mensah et al, 1998;Kanabar et al, 2005). Heparin acts as a potent competitive inhibitor of inositol 1,4,5-triphosphate-dependent calcium release from the endoplasmic reticulum (Ghosh et al, 1988), an effect that is considered to underlie the inhibition of human mast cells that has been described in vitro (Inase et al, 1993) and found to be independent of anticoagulant activity (Ahmed et al, 1997).…”
Section: A Effects Of Heparin On Inflammation and Inflammatory Mediamentioning
confidence: 99%